Criminological and Victimological Analysis of the Crime of Sextortion in Video Call Sex (VCS)In the Digital Age - Gayatri, Nungky Dwi; Supriadi, Moh; Akadol, Nina Septiana Jasri; Mukti, Plasma Versiana; Yuliana; Natalia, Kristiani (KRTHA BHAYANGKARA, 2025)
Sextortion (sexual extortion) is a crime that exploits the vulnerability of the victim through the threat of distributing material containing pornography, for certain purposes such as financial gain, sexual gratification, or even psychological domination. However, sometimes what was originally intended as a proof of trust often turns into a tool of blackmail when the relationship is in conflict. So that victims are usually forced to do things that the victim does not want, but the perpetrator wants. Along with the development of ITE and the increasing use of digital applications, the crime of Sextortion is increasingly massive in video call sex (VCS), where men who are educated, intellectual, and have prominent positions become objects of sexual extortion. This article critically examines the root causes of various factors behind the occurrence of sextortion crimes on social media platforms?; and what is a holistic approach to address the driving factors for the crime of sextortion? This type of research is empirical juridical, by examining the applicable positive legal norms and their implementation in community practice. Data is collected through document studies and in-depth interviews as the primary information collection techniques. This article emphasizes the importance of comprehensive victim protection through trauma recovery services, legal assistance, and public education about digital security. A multidisciplinary approach that is on the side of victims is a crucial step in building a criminal justice system that is responsive to sexual crimes in the digital age